Fourth issue of real-time image processing - Carlsohn, Matthias F.; Kehtarnavaz, Nasser (Journal of real-time image processing, 2008)
The mutual fertilization between JRTIP and the SPIE annual Conference on Real-time Image and Video Processing (EI109: 18–22 January 2009, San Jose Convention Center, San Jose, CA, United States) has generated additional synergies and strengthened the focus of this community as indicated in the subjects of several JRTIP special issues covering “hot-spots” of the field of real-time image and video processing. [...]it is worth mentioning that we are working towards having JRTIP listed in the scientific citation index ISI (formally Institute for Scientific Information and now Thomson Scientific) based on 3 years of increasing success with JRTIP plus the added value of 11 years of experience with the journal of “Real-Time Imaging” (Elsevier) by many of the associate editors. The final two articles describe applications for segmentation: one for color segmentation in the HSI space for an automotive scenario and the second one presents a fast region segmentation algorithm using a line segment table.